Frontal sinus ontogeny and covariation with bone structures in a modern human population : base de datos - Ventrice, Fernando (2017)
Fil: Ventrice, Fernando. Laboratorio de Neuroimágenes. Departamento de Imágenes. Instituto de Investigaciones Neurológicas Raúl Carrea. FLENI. Buenos Aires; Argentina